Importance of Male Fertility Control in Family Planning - R.P. Tulsiani, Daulat; Abou-Haila, Aida (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2014)
The world population, currently estimated to be almost seven billion, is expected to double in less than four decades. The projected population growth will cause severe competition for existing resources, not to mention the issue of overcrowding of the planet and additional greenhouse gases that will have an adverse effect on the ecological health of the planet. A recent survey conducted by the United Nations Population Control Division shows that the majority of today’s young men in many countries are willing to participate in family planning by taking full control of their fertility, an important global health issue. However, the contraceptive needs of tens of millions of men/couples go unmet every single day and results in millions of unwanted pregnancies. Ever since the approval of the birth control pill by the Food and Drug Administration (FDA) in 1960, scientists have been hoping for a male equivalent. It has, however, been a difficult road, in part because of the complicated science of the male reproductive system. It is easier to control a monthly event of ovulation in women than to regulate the production of millions of fertile spermatozoa every day in men. Thus, the contraceptive options for men have not changed in decades and are still limited to the use of condoms, a timely withdrawal/pulling out (coitus interruptus) or vasectomy, a minor surgical procedure in which the vas deferens is occluded to prevent the release of spermatozoa during ejaculation. The first two approaches have a relatively higher failure rate, whereas the last approach is largely irreversible and not suitable for younger men. In this article, we will discuss various approaches currently available for men to take control of their fertility. Our intention is to discuss the details of three similar approaches that will provide safe, affordable and reversible contraception for men and are close to being approved for use by millions of men around the globe. The availability of safe, reversible and reliable male contraceptives will allow men and women to take full control of their fertility in family planning.
Keywords: male contraception